Immobilization of poly(L-lactide)-degrading enzyme from Laceyella sacchari LP175: characterization and evaluation for hydrolysis of poly(L-lactide) polymer - Lomthong, Thanasak; Lumyong, Saisamorn; Marty, Alain; Kitpreechavanich, Vichien (Progress in Applied Science and Technology, 2018)
Poly(L-lactide) (PLLA)-degrading enzyme from the thermophilic filamentous bacterium, Laceyella sacchari LP175, was entrapped in calcium alginate beads and characterized using emulsified PLLA as a substrate. The 1.0% sodium alginate appeared to be the most effective for the immobilization, with 60% actual immobilization efficiency and 80% theoretical immobilization efficiency. Immobilized enzyme represented emulsified PLLA hydrolyzing activity similar to free enzyme. The immobilized enzyme showed an operational stability up to five times that of the free enzyme, indicating that it is a suitable choice for applications to hydrolysis the PLLA polymer due to reduced enzyme preparation costs. The optimum temperature and thermal stability of the immobilized PLLA-degrading enzyme were shifted from 60 to 65 oC and 55 to 70 oC, respectively, while the pH optima and stability remained unaltered. The immobilized enzyme showed a higher stability at 60 oC for up to 12 h and improved the lactic acid tolerance ability up to 10% (v/v) as compared to the free enzyme which could help avoid lactic acid feedback inhibition during hydrolysis. Hence, the PLLA-degrading enzyme from L. sacchari LP175 was more stable after immobilization and represented a highly appropriate choice for the recycling process of emulsified PLLA polymer.